(untitled) (Research, Society and Development, 2021)
The cultivation of sunflower plants is hampered by the scarcity of nutrients, mainly nitrogen (N), phosphorus (P) and potassium (K), which can affect the production of grains and oil. The objective of this study was to evaluate the growth and development of sunflower grown under fertilization levels with NPK formulations of mineral and organomineral origin applied at sowing. The experiment was carried out in plastic pots filled with 30 L of dystrophic Red Latosol soil, collected from the 0.0 to 0.2 m layer, located in an experimental area of the Instituto Federal Goiano, in the municipality of Rio Verde, GO. The experimental design used was the randomized blocks analyzed in a 4 × 2 factorial scheme (applications and sources of N-P-K), with three replications. The applications were in the dosages of 50%, 100%, 150% and 200% of the recommendation for the culture and the sources of N-P-K were mineral and organomineral. The parameters of growth and leaf area of sunflower plants were evaluated at 30, 60 and 90 days after sowing. The mineral source NPK provides greater stem diameter, number of leaves and leaf area of the sunflower at 30 and 60 days after sowing and plant height at 30, 60 and 90 days after sowing, compared to the organomineral source.